Psychometric Analysis of a Postulated Set of Evolved Human Motives - Aunger, Robert; Foster, Dugald; Curtis, Val (Frontiers in Psychology, 2021)
Many different general systems of human motives have been postulated in the psychological literature. However, as yet, no consensus on which motives should be nominated, nor how many there are, has emerged. Recently, we deduced the existence of a number of motives using a logical argument derived from evolutionary theory; that humans have evolved an independent psychological “engine” to respond to each kind of evolutionary problem set by a dimension of the human niche, or life-way. Here, we confirm the existence of 14 out of 15 of these postulated motives using factor analysis on a web-based sample of 500 respondents from the UK: Lust, Hunger, Fear, Disgust, Attract, Love, Nurture, Hoard, Create, Affiliate, Status, Justice, Curiosity, and Play. The items which loaded most strongly for each factor confirmed the expected core value of each motive. Comfort did not emerge, perhaps because it is more about satisfying specific physiological requirements than a cluster of activities linked semantically by the concept of attaining “comfort.” We believe this analysis can form the foundation of a scale for use in applied psychological work ranging from personality testing to personnel selection to public health program design.